2022
DOI: 10.3390/ma15093155
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of a Novel Vanillin-Containing DOPO Derivate as a Flame Retardant for Epoxy Resins

Abstract: A novel bio-based flame retardant designated AVD has been synthesized in a one-pot process via the reaction of 9,10-dihydro-9-oxa-10-phospha-phenanthrene-10-oxide (DOPO), vanillin (VN), and 2- aminobenzothiazole (ABT). The structure of AVD was confirmed using Fourier transform infrared spectroscopy (FTIR), and 1H and 31P nuclear magnetic resonance spectroscopy (NMR). The curing process, thermal stability, flame retardancy, and mechanical properties of the epoxy resin (EP) modified with AVD have been investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…C1s spectrum was deconvoluted into C C/C H (284.7 eV), C O C (285.6 eV), and C O (289.3 eV) peaks. 28 The peaks at 536.7, 532.8, and 530.8 eV in the O1s spectrum were attributed to COOH, C O P, and P O, respectively. For N1s spectrum, the peaks at 398.4, 400.2, and 403.4 eV were ascribed to pyridine nitrogen, pyrrole nitrogen, and nitrogen oxide.…”
Section: Flame-retardant Mechanismmentioning
confidence: 97%
See 2 more Smart Citations
“…C1s spectrum was deconvoluted into C C/C H (284.7 eV), C O C (285.6 eV), and C O (289.3 eV) peaks. 28 The peaks at 536.7, 532.8, and 530.8 eV in the O1s spectrum were attributed to COOH, C O P, and P O, respectively. For N1s spectrum, the peaks at 398.4, 400.2, and 403.4 eV were ascribed to pyridine nitrogen, pyrrole nitrogen, and nitrogen oxide.…”
Section: Flame-retardant Mechanismmentioning
confidence: 97%
“…For instance, an EP loaded with 7.5 wt% of a novel DOPO-based flame retardant (AND) obtains a UL-94 V-0 rating and 31.3% LOI. 28 Unfortunately, its tensile and flexural strengths reduced by 32.5% and 10.33%, compared with the neat EP. Hence, challenges still remained in developing a novel EP flame retardant with superior comprehensive properties.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[12][13][14][15] There has been reported that the flame-retardant efficiency of DOPO can be further improved through the molecular design method. [16][17][18] Thereinto, introducing the nitrogen-containing group (such as triazine, [19,20] triazinetrione, [21][22][23] Schiff-base, [24][25][26] and hexachlorocyclotriphosphazene [27,28] ) is a feasible way. The phosphophenanthrene group and nitrogen-containing group can exert a P−N synergistic flame-retardant effect to improve the flame retardancy of epoxy thermosets.…”
Section: Introductionmentioning
confidence: 99%
“…However, a high content of DOPO groups is required to achieve a significant improvement in the flame resistance of epoxy resins, which can lead to a deterioration of the end-use product’s characteristics. Therefore, the DOPO monomer has been frequently appealed in the synthesis of various flame retardants containing nitrogen, sulfur, silicon, or boron in the structure, elements well-known for their synergistic effect in terms of flame retardancy when used along with phosphorus, thus, showing better flame retardancy in epoxy-resin-based materials [ 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Various diamines and bisphenols containing phosphorus and nitrogen as reactive flame retardants for crosslinking epoxy resin have been reported [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%